RELEVANCE OF STATE SOCIALISM IN THE CONTEXT OF POLITICAL ECONOMY OF CURRENT SCENARIO (International Journal of Food and Nutritional Sciences, 2021)
State Socialism of Dr.Ambedkar presents the blueprint of the model of economic development. It advocates for nationalisation of key industries, basic industries and of agricultural land. In his concept of State Socialism Dr.Ambedkar maintained equilibrium between individual liberty and State control. He was not opposed private sector of the economy. Dr.Ambedkar attempted to establish State Socialism in the Democratic setup by the law of the Constitution and to make it unalterable part of the Constitution. He thought to incorporate State Socialism in the Fundamental Rights of the Constitution as part III of the Chapter on Fundamental Rights, so that no parliamentary majority can amend, suspend or abrogate it. But Constituent Assembly turned down his notion on grounds that the provision did not relate to Fundamental Rights. Instead, India adopted policy of Democratic Socialism, which assigned the job of implementing socialist policy to the will of the legislature, i.e., to the parliamentary majority.